Unveiling the dynamics and impact of emotional presence in collaborative learning - Tan, Siaw Eng; Jung, Insung (International Journal of Educational Technology in Higher Education, 2024)
This study aims to understand the dynamics and impact of emotional presence in a collaborative learning environment and its effects on the learning process and outcomes. Emotional presence, defined as the experience of emotion arising from cognitive appraisals in learner-environment interactions, encompasses four dimensions: interest-curiosity, emotional regulation, expression management, and emotional awareness. Using a mixed-methods approach, we surveyed 33 Japanese college students engaged in collaborative learning activities and conducted in-depth interviews with 10 participants to gather qualitative insights. The study revealed that emotional presence evolves throughout the collaborative process, with increased emotional regulation in response to complex tasks, reflecting learners’ adaptations to varying task demands. It highlighted the importance of emotional regulation in shaping the learning process and improving outcomes in collaborative learning. Our findings suggest that heightened emotional presence, with increased emotional awareness and regulation, fosters cognitive development and learner well-being, supporting more effective and fulfilling collaborative learning experiences. The study also emphasizes the crucial role of cognitive appraisal in shaping emotional experiences, significantly influencing outcomes in technology-enhanced environments. The study concludes by proposing future research directions, such as examining the longitudinal impacts of emotional presence and exploring interventions to enhance emotional regulation skills in diverse learning contexts.